Efficacy of Alendronate for Preventing Collapse of Femoral Head in Adult Patients with Nontraumatic Osteonecrosis. (11th November 2014) - Hong, Yu-Cai; Luo, Ru-Bin; Lin, Tiao; Zhong, Hui-Ming; Shi, Jian-Bin
Abstract : The purpose of the current review was to determine the efficacy of alendronate for preventing collapse of femoral head in adult patients with nontraumatic avascular osteonecrosis of femoral head (ANFH). Five randomized controlled trials (RCTs) involving 305 hips were included in this review, of which 3 studies investigated alendronate versus control/placebo and the other 2 studies compared the combination of alendronate and extracorporeal shockwave therapy (ESWT) with ESWT alone. Our results suggested that even the patients with extensive necrosis encountered much less collapse in the alendronate group than control group. In these RCTs, their data also indicated a positive short- and middle-term efficacy of alendronate treatment in joint function improvement and hip pain diminishment. With the presence of the outlier study, only insignificant overall efficacy of alendronate could be observed with substantial heterogeneities. In addition, we did not find any additive benefits of alendronate in combination with ESWT for preventing collapse compared to ESWT alone. In conclusion, there is still lack of strong evidence for supporting application of alendronate in adult patients with nontraumatic ANFH, which justified that large scale, randomized, and double-blind studies should be developed to demonstrate the confirmed efficacies, detailed indication, and optimized strategy of alendronate treatment.